The General Irrelevance of the General Impossibility Theorem - Tullock, Gordon (Quarterly Journal of Economics, 1967)
Aggregation of preferences, 256. — The paradox of voting and its significance, 257. — Voting in a simple model, 258. — Some complications, 260. — Unimportance of the paradox, 263. — Voting in a more realistic model, 264. — Conclusion, 270.